Novel methods to evaluate fish response to stress. (Research'eu results magazine)
Farmed fish are subjected to many stressors that have an important impact on their health and can even lead to their death. The COPEWELL project tried to help fish farmers to cope with this issue by developing methods that will allow them to better understand how fish experience their world.